Improvisación Libre: una perspectiva performativa en el campo musical expandido de la ciudad de Córdoba hacia los últimos diez años (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2021)
The article analyzes the recent microhistory of the city of Córdoba around contemporary musical practice and music teaching institutions. The economy of symbolic goods and cooperative bonds in the city are reviewed to propose, from free improvisation, an expansion of the local musical field.
Keywords: Free Improvisation; Practice; Bonding; Contemporary Music; Expansion